dukungan Dukungan Keluarga Terhadap Tingkat Kecemasan Pada Pasien Tumor Payudara - Nurpadila Dila Nurpadila (LPPM STIKES Marendeng Majene, 2021)
Patients with breast tumors need support from their families because family support is very influential on mental in the form of enthusiasm, empathy, trust, attention so that family members who are in a condition experiencing breast tumors see that the family is always supportive and ready to provide help and assistance if needed. The study was conducted in the surgical poly room of the Majene Regency General Hospital in 2017. The research objective was identified